الأَبْعَادُ البَلَاغِيَّةُ والصَّرْفِيَّةُ فِي اللَّهَجَاتِ الجَزَائِرِيَّةُ – اللَّهْجَةُ السُّوفِيَّةُ أُنْمُوذَجًا –: Rhetorical and Morphological Dimensions in Algerian Dialects - The Dialect of Oued Souf is a Model - - ضو خالد (Maalim, 2021)
This research studies the rhetorical cases in the Algerian dialects, and focuses on its examples on the dialect of Oued Souf. And the research aims to highlight the importance of the fundamentalist view of languages and dialects in understanding words and perception of meanings. And it also aims to introduce the Sufi dialect and its origins, and rooting some of the rhetorical and morphological foundations in it, and among the most important results the research found that the Souf dialect is one of the most eloquent Algerian dialects; because of its uses of metaphor and rhetoric. In addition, it is distinguished from other dialects through its use of femininity in the plural pronouns of the feminine, and its use of the absent person pronoun in masculine singular